Leading with Purpose and Awareness: Integrating Mindfulness, Emotional Intelligence, and Gender Balance for Organisational Success - Agarwal, Vikash (Digital Repository of Theses, 2025)
This research examines the interplay between leadership styles, awareness, gender dynamics, and their influence on organizational productivity, motivation, and employee satisfaction. As organizations strive for inclusivity and efficiency in an increasingly diverse workplace, understanding how leadership can adapt to individual and collective needs is imperative. Employing a mixed-methods approach, data was collected through LinkedIn responses, surveys, interviews, and case studies of prominent organizations. The study drew insights from global leaders, capturing diverse perspectives on leadership practices and challenges. Analysis revealed key themes, including the significance of personalized motivation strategies, the role of self-awareness in leadership, and the impact of fostering an inclusive culture. Findings highlighted that effective leadership transcends gender but requires adaptability to individual personalities, cultural contexts, and organizational goals. Leaders who prioritize empathy, transparent communication, and a shared vision cultivate higher levels of trust and collaboration among team members. While differences in motivation patterns between men and women were observed, they were more nuanced and context-dependent than generalized assumptions suggest. Emotional intelligence emerged as a cornerstone for leaders to navigate complex interpersonal dynamics and build resilient teams. The research also unveiled innovative practices from organizations such as Microsoft, Google, and Tesla, emphasizing creativity, self-awareness, and transformational leadership as drivers of success. A novel contribution of this study lies in its integration of diverse data sources to provide actionable insights for leaders and policymakers. In conclusion, the study underscores the importance of leadership that is both flexible and grounded in core values of inclusivity and respect. It offers recommendations for fostering a balanced leadership approach that meets the evolving demands of modern workplaces. This research invites further exploration into the intersection of leadership, awareness, diversity, and innovation, aiming to equip organizations with strategies for sustained growth and employee well-being.